PARTIES AS A KEY LINK OF CIVIL SOCIETY (Conferencea, 2022)
The article covers the third stage of development of civil society in the current period - the beginning of the XX-XXI centuries. During this period, civil society and the rule of law became the market economy, democracy, the idea of the nation, the nation-state became universal wealth, and the formation of political pluralism, freedom of speech, freedom of the press, freedom of the press and multiparty system